PROSPEK BUDIDAYA KEDELAI PADA LAHAN SAWAH TADAH HUJAN DAN SAWAH IRIGASI SEDERHANA UNTUK PENINGKATAN PRODUKSI KEDELAI DI INDONESIA - Winardi Winardi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
Development of soybean in acidic dry soils having problems because the soil is relatively infertile. Further more in the irrigated paddy field especially technical irrigation, soybean commodity got competition from other commodities, especially rice on the Rainy Season and other commodities, such as corn and water melon on the Dry Season. This review describes the prospects of rainfed and simple irrigated rice field for the development and improvement of soybean production in Indonesia. Of 7,750,329 ha of total rice fields in Indonesia, rainfed rice field covers 2,017,642 ha (26.03%) and simple irrigated rice field1, 588,051 ha (20.49%). Distribution ofthe two types of rice field in a row in some provinces are as follows: Central Java (273,973 and 195,072 ha), East Java (242,562 and 119,019 ha), West Java (161,859 and 250,855 ha), Banten (88,672 and 42,602 ha), North Sumatra (149,547 and 120,835 ha), and South Sulawesi (247,191 and 156,393 ha). Rainfed and simple irrigated rice field with fluctuating water availability appropriate to cultivate onetime rice and one-time secondary crops. Recommended secondary crops in the rainfed and simplel irrigated rice field, such as corn and soybeans. In the Island of Java, in the cropping pattern of Rice-soybean, rice grown in the Wet Season and soybeans in the first Dry Season. While in the cropping patern of Soybean-rice, soybeans planted in early Rainy Season before planting rice. The advantages of soybean cultivation in rainfed and simple irrigated rice field can increase the harvest index (IP), breaking the cycle of pests and diseases, improve efficiency (without or minimum tillage, utilizing there sidual fertilizer, weed grow this relatively unheavy, utilize the remaining soybeanas green manure). Soybean varieties that suitable for paddy fields generally have early to moderate maturity (75-95 days). Of 18 soybean varieties suitable for paddy field, including 10 varieties of large seed size (13.5 to 18.5 g/100 g) and favored by tempe and tofu maker. Soybean productivity in the rainfed or simple irrigated rice field reach 2.5-3.0 t/ha. Keywords: soybean; cultivation; rainfed rice field; simple irrgated rice field.